Optimization of Test Management in Maluku Health Analyst Department - M Natsir, Ramdhani (Sriwijaya Journal of Medicine, 2020)
Introduction. Exam management is crucial in the implementation of evaluation in educational institutions. This isbecause the test implementation process is one of the determinants of the quality of an institution. This study aims toassess the optimization of examination management in the health analyst department of the Health Polytechnic of theMinistry of Health in Maluku. Methods. This study used a descriptive research design. This research was conducted inthe health analyst department of the Maluku Health Polytechnic Ministry of Health in July - August 2019. The samplein this study were all employees and students in the Maluku Health Poltekkes Department of Health analyst with thesampling technique using total sampling. A Likert scale questionnaire was used as an instrument in the study. Results.There are respondents with more job distribution, namely 45 students (80.4%). Respondents who rated theapplication and website development category as very satisfied were 30 respondents (53.5%), and satisfied were 26respondents (46.5%). Respondents who assessed the optimal management of the examination category were verysatisfied with 38 respondents (67.8%), and satisfied with 18 respondents (32.2%). Conclusion. There is no relationshipbetween the implementation of the SOP for exam management with optimal exam management, and there is arelationship between making applications and websites with optimal exam management.